2022
DOI: 10.1109/access.2022.3217770
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Learning Approach to Evaluate Factors Associated With Post-Traumatic Stress Symptoms in Physicians: Insights From the COVID-19 Pandemic

Abstract: Physicians facing the COVID-19 pandemic are likely to experience acute and chronic, and often unpredictable, occupational stressors that can incur post-traumatic stress symptoms (PTSS), prevention of which is of utmost importance to enhance healthcare workforce efficiency. Unlike previous studies, in this paper we developed a generalized data-driven framework to generate insights into the complex, nonlinear associations of cognitive/occupational factors with physicians' PTSS-risk. Data were collected from prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 118 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…A study of the Post-Traumatic Stress Symptoms (PTSS) in physicians on the frontlines of COVID-19 was presented in [12]. The objectives of the study were (1) to evaluate the symptoms of PTSS among frontline physicians compared to second-line ones, (2) to identify the higher-risk group among them, (3) to predict the PTSS risk in the higher-risk group using ML algorithms, and (4) determine possible patterns between the predictors.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…A study of the Post-Traumatic Stress Symptoms (PTSS) in physicians on the frontlines of COVID-19 was presented in [12]. The objectives of the study were (1) to evaluate the symptoms of PTSS among frontline physicians compared to second-line ones, (2) to identify the higher-risk group among them, (3) to predict the PTSS risk in the higher-risk group using ML algorithms, and (4) determine possible patterns between the predictors.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Research has demonstrated that depersonalization is the most serious aspect of burnout in terms of its impact on functioning (4) and that exhaustion, on its own, does not constitute burnout, as evidenced by its quick reversal when staff are provided with more rest (7). Finally, although the PTSD scale used cannot be regarded as diagnostic, the findings did suggest that these symptoms were elevated, as they have been found to be in other large samples of critical care workers in relation to working during the pandemic (8).…”
mentioning
confidence: 95%
“…Given the predominance of cardiovascular dysfunction and coronary anomalies identified in early reports of MIS-C (12), much of the initial literature describing postdischarge outcomes following MIS-C appropriately focused on cardiac outcomes. Reassuringly, studies evaluating patients 6 to 12 months following MIS-C have demonstrated normalization of cardiac function, resolution of coronary dilation or aneurysms, and no signs of persistent myocardial inflammation in most patients (2,4,8,9). Activity impairment and exercise intolerance have been more commonly reported in the months following hospitalization for MIS-C (4,6).…”
mentioning
confidence: 99%
See 2 more Smart Citations